RELATIONSHIP BETWEEN FACTORS OF MARKETING COMMUNICATION WITH SPECIAL REFERENCE TO ORGANISED RETAILERS IN KERALA - N. Uma Devi & Vipin V (International Journal of Research and Analytical Reviews, 2018)
Synergic effect created by integration of marketing communications is often impressive; but, for synergy to work integrated marketing communications tool should be related and adaptive with one another. This study probes relationship between factors of marketing communication by organised retailers in Kerala.